Electrospun fluorescent sensors for the selective detection of nitro explosive vapors and trace water. Issue 38 (18th September 2018) - Wu, Wandan; Shi, Naien; Zhang, Jun; Wu, Xiaodong; Wang, Tao; Yang, Lei; Yang, Rui; Ou, Changjin; Xue, Wei; Feng, Xiaomiao; Xie, Linghai; Huang, Wei
Abstract : Electrospun composite fluorescent sensors for selective discrimination of nitro explosives and trace water were developed. Abstract : For the practical applicability of fluorescent sensors for explosives, it is significantly important to discriminate between nitro explosives and water-based interferents, due to the unavoidable need for detection in commonly humid fields or conditions. Herein, we made a detailed investigation on the sensing selectivity of highly sensitive fluorescent sensors of polystyrene/9-(pyren-1-yl)-9 H -carbazole (PS/PyCz) nanofibers and polyethylene oxide/9-(pyren-1-yl)-9 H -carbazole (PEO/PyCz) nanofibers fabricated via a facile low-cost electrospinning strategy. It was found that PEO/PyCz nanofibers exhibit a sensitive response to nitro explosive vapors, but they cannot resist interference from non-nitro substances encountered in daily-life, including water, perfume, orange juice, wine, etc. It was demonstrated that the excited PyCz molecules would lose energy due to enhanced molecular rotation in water-based PEO/PyCz nanofibers. Because of a favorable photo-induced electron transfer driving force between the PyCz fluorophore and nitro explosives, the fluorescence of the materials resulted in similar strong responses to the explosives. However, the PS/PyCz nanofibrous film can detect not only nitro explosive vapors with high sensitivity, but also exhibits high selectivity over the typical common water-based interferents due to its hydrophobicity. This work provides a new aspect for fluorescent sensor design and component control for the reliable identification of nitro explosives in practical application fields for controlling environmental pollution, combating terrorism and improving national security.